Intrinsic Exercise Capacity and Mitochondrial DNA Lead to Opposing Vascular-Associated Risks. Issue 1 (3rd November 2020) - Roy, Shaunak; Edwards, Jonnelle M; Tomcho, Jeremy C; Schreckenberger, Zachary; Bearss, Nicole R; Zhang, Youjie; Morgan, Eric E; Cheng, Xi; Spegele, Adam C; Vijay-Kumar, Matam; McCarthy, Cameron G; Koch, Lauren G; et al.
Abstract: Exercise capacity is a strong predictor of all-cause morbidity and mortality in humans. However, the associated hemodynamic traits that link this valuable indicator to its subsequent disease risks are numerable. Additionally, exercise capacity has a substantial heritable component and genome-wide screening indicates a vast amount of nuclear and mitochondrial DNA (mtDNA) markers are significantly associated with traits of physical performance. A long-term selection experiment in rats confirms a divide for cardiovascular risks between low- and high-capacity runners (LCR and HCR, respectively), equipping us with a preclinical animal model to uncover new mechanisms. Here, we evaluated the LCR and HCR rat model system for differences in vascular function at the arterial resistance level. Consistent with the known divide between health and disease, we observed that LCR rats present with resistance artery and perivascular adipose tissue dysfunction compared to HCR rats that mimic qualities important for health, including improved vascular relaxation. Uniquely, we show by generating conplastic strains, which LCR males with mtDNA of female HCR (LCR-mt HCR /Tol) present with improved vascular function. Conversely, HCR-mt LCR /Tol rats displayed indices for cardiac dysfunction. The outcome of this study suggests that the interplay between the nuclear genome and the maternally inherited mitochondrial genome with high intrinsic exercise capacity is a significant factor for improved vascular physiology, and animal models developed on an interaction between nuclear and mtDNA are valuable new tools for probing vascular risk factors in the offspring. Graphical Abstract: